Unravelling molecular complexity in structural cell biology - Pfeffer, Stefan; Mahamid, Julia (Current opinion in structural biology, 2018)
Structural and cell biology have traditionally been separate disciplines and employed techniques that were well defined within the realm of either one or the other. Recent technological breakthroughs propelled electron microscopy of frozen hydrated specimens (cryo-EM) followed by single-particle analysis (SPA) to become a widely applied approach for obtaining near-atomic resolution structures of purified macromolecules. In parallel, ongoing developments on sample preparation are increasingly successful in bringing molecular views into cell biology. Cryo-electron tomography (cryo-ET) has so far served as the main imaging modality employed in these efforts towards obtaining three-dimensional (3D) volumes of heterogeneous molecular assemblies. We review the state-of-the-art in cryo-ET and computational processing and describe the current opportunities and frontiers for in-cell applications.